Perancangan Komik Digital Interaktif "New Ethnicia" : Eksplorasi Visual Storytelling Cerita Rakyat Indonesia - Rizal A. Dzulfiqar; Alvanov Zpalanzani Mansoor (Wimba : Jurnal Komunikasi Visual, 2014)
Indonesian folkloree in comic form is still difficult to compete with foreign-made comics both in quality and quantity. Moreover, with Indonesiaâs teens as target market who tend to like comics from abroad, Indonesiaâs folkloree and content in comic may be neglected. In order to prevent those conditions, it required an alternative solution to packaging folkloree through popular visual media among teens such as mobile device. Interactive digital comics in mobile devices may support the presentation of Indonesian folkloree, as long as it designed with the appropriate interactive storytelling and media strategy. This is an action research that delivering solution in form of adigital comic prototype. Through selected aspects of visual storytelling and interactivity theory, data will be analyzed to produce the digital comic formulation from Indonesia folkloree which will work as the foundation of designing interactive digital comics on mobile devices. As the result, the Indonesiaâs folkloree can be delivered through a formulation of combined interactive storytelling and media strategy.